2015
DOI: 10.1007/s00404-015-3745-7
|View full text |Cite
|
Sign up to set email alerts
|

Maternal serum copeptin, MR-proANP and procalcitonin levels at 11–13 weeks gestation in the prediction of preeclampsia

Abstract: The maternal serum copeptin, MR-proANP and PCT levels are higher in EO-PE and LO-PE patients, but the difference is not significant. Thus, their levels in first trimester are not proven to be effective markers to screen for PE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 38 publications
4
13
0
Order By: Relevance
“…Copeptin, a glycosylated polypeptide consisting of the 39 C-terminal amino acids of arginine vasopressin, has been suggested as “a new biomarker that is specific for preeclampsia” (712), and certainly changes during its development (713). However, it turns out that it is also essentially a measure of all kinds of stresses and adverse events (714719), including those caused by infection (720729).…”
Section: Proteomic and Similar Biomarkers – Circulating And Placentalmentioning
confidence: 99%
“…Copeptin, a glycosylated polypeptide consisting of the 39 C-terminal amino acids of arginine vasopressin, has been suggested as “a new biomarker that is specific for preeclampsia” (712), and certainly changes during its development (713). However, it turns out that it is also essentially a measure of all kinds of stresses and adverse events (714719), including those caused by infection (720729).…”
Section: Proteomic and Similar Biomarkers – Circulating And Placentalmentioning
confidence: 99%
“…Another study comprising 50 pregnant women with PE, 54 healthy pregnant women and 33 non-pregnant women, concluded that copeptin was a strong predictor for the development of PE in all three trimesters of pregnancy, with areas under the curve (AUC) of 0.90, 0.90 and 0.78, respectively 9 . Conversely, two smaller studies were unable to demonstrate such findings 8,18 . Sugulle et al 6 measured MR-proANP at 24 to 42 weeks' gestation in 77 normotensive and 107 PE pregnancies and found that MR-proANP had an AUC of 0.85 in discriminating between PE pregnancies and normotensive pregnant controls, which was inferior to that of sFlt-1 (AUC, 0.94).…”
Section: Discussionmentioning
confidence: 93%
“…A potential pathogenic role of arginine vasopressin in preeclampsia was proposed based on elevated circulating concentrations of copeptin. Most (Zulfikaroglu et al, 2011;Santillan et al, 2014;Yeung et al, 2014;Tuten et al, 2015), but not all (Birdir et al, 2015) groups reported elevated circulating copeptin levels before and/or during the clinical manifestations of the disease. In one study, the increase in copeptin concentrations measured at 16 weeks of gestation was specific for preeclampsia, not being observed in women who developed gestational hypertension (without proteinuria), gestational diabetes mellitus or preterm birth in the absence of preeclampsia (Yeung et al, 2014).…”
Section: Arginine Vasopressin Receptorsmentioning
confidence: 98%